2022
DOI: 10.1002/hep.32738
|View full text |Cite
|
Sign up to set email alerts
|

AIF1 + CSF1R + MSCs, induced by TNF‐α, act to generate an inflammatory microenvironment and promote hepatocarcinogenesis

Abstract: Background and Aims: Increasing evidence suggests that mesenchymal stem cells (MSCs) home to injured local tissues and the tumor microenvironment in the liver. Chronic inflammation is regarded as the major trait of primary liver cancer. However, the characteristics of endogenous MSCs in the inflammatory environment and their role in the occurrence of liver cancer remain obscure. Approach and Results: Using single-cell RNA sequencing, we identified a distinct inflammation-associated subset of MSCs, namely AIF1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…Research by YANG et al also demonstrated that AIF-1 was an independent prognostic indicator that regulates the βcatenin signaling pathway in gastric cancer [40]. AIF-1 + CSF1R + MSCs, induced by TNF-α, generate an inflammatory microenvironment and promote hepatocarcinogenesis [41]. Furthermore, the PAK5-AIF signaling pathway may play an essential role in mammary tumorigenesis, providing a new therapeutic target for breast cancer treatment [42].…”
Section: Discussionmentioning
confidence: 99%
“…Research by YANG et al also demonstrated that AIF-1 was an independent prognostic indicator that regulates the βcatenin signaling pathway in gastric cancer [40]. AIF-1 + CSF1R + MSCs, induced by TNF-α, generate an inflammatory microenvironment and promote hepatocarcinogenesis [41]. Furthermore, the PAK5-AIF signaling pathway may play an essential role in mammary tumorigenesis, providing a new therapeutic target for breast cancer treatment [42].…”
Section: Discussionmentioning
confidence: 99%
“…Tumour volume was calculated using the formula: tumour volume (mm 3 ) = (smallest diameter 2 × largest diameter)/2. 38 The venous blood of mice was drawn from the eye orbit of mice, and then the mice were sacrificed at 3 weeks after the last irradiation. The levels of AST and ALT in serum were detected by an automatic biochemistry analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…Tumour volume and liver/body weight ratio were evaluated at 3 weeks after the last irradiation. Tumour volume was calculated using the formula: tumour volume (mm 3 ) = (smallest diameter 2 × largest diameter)/2 38 . The venous blood of mice was drawn from the eye orbit of mice, and then the mice were sacrificed at 3 weeks after the last irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15][16][17] Preclinical and clinical studies have verified that the MSCs can mediate T cells activation and transform the function of dendritic cells and macrophages. [16,[18][19][20][21][22][23] However, MSC therapy has not achieved its desired clinical potential in IBD treatment because the therapeutic activity of naive seeding cells is limited. [24][25][26][27][28] In addition, existing intravenous injection strategy is generally systemic with several limitations such as poor targeting and fast metabolism.…”
Section: Introductionmentioning
confidence: 99%